Penggunaan Model PBL Untuk Meningkatkan Hasil Belajar IPA Materi Suhu Dan Kalor Sekolah Dasar - Pinang Sari, Mutiara; Rini, Riswanti (JUPE : Jurnal Pendidikan Mandala, 2023)
The classroom action research conducted by the researchers aims to improve the learning outcomes of fifth grade students at SD Negeri 2 Hajimena, especially in science lessons on temperature and heat. The research was conducted for approximately 3 months. The background of this research is the low student learning outcomes, there are still many educators delivering science learning material only with lectures so that the illustrations captured by students are also still abstract. Delivering material by educators in lectures makes the learning process dominated by educators and only a few students. The lack of students' role in the learning process will cause students to be passive, bored, and bored. This research was conducted by several stages including action, test and observation. The results showed that there was an increase in student learning outcomes influenced by the PBL Model. The increase in the value of science learning outcomes on temperature and heat by students could be seen from before the action was taken, namely in the pre-cycle only 8 students (38.9%) completed, after the action was taken on The first cycle of students who passed increased to 11 students (52.38%), and after the action was taken in the second cycle the students who passed increased to 18 students (85.71%). This research was successful because it had reached the set indicators, namely ≥80% of all students with KKM ≥75.